Irisin promotes growth, migration and matrix formation in human periodontal ligament cells. (March 2020) - Pullisaar, Helen; Colaianni, Graziana; Lian, Aina-Mari; Vandevska-Radunovic, Vaska; Grano, Maria; Reseland, Janne Elin
Highlights: Irisin enhances human periodontal ligament cell growth and migration. Irisin steers human periodontal ligament cells to differentiate into osteoblasts. Irisin may be feasible for regeneration of periodontal hard tissue defects. Abstract: Objective: The objective of the study was to examine the effect of irisin on human periodontal ligament cells (hPDLCs) growth, migration and osteogenic behaviour in vitro . Materials and methods: Primary hPDLCs and human osteoblasts (hOBs), used as positive controls, were cultured with irisin (10 and 100 ng/ml), and effect on cell proliferation was evaluated with 5-bromo-2`-deoxyuridine incorporation at 1, 2, and 3 days, and on migration capacity was investigated by scratch assay at 2, 6, and 24 h. Osteogenic behaviour was assessed with alkaline phosphatase activity, immunoassay at 3, 7, 14, and 21 days, and confocal laser scanning microscopy at 21 days. Mineralization was examined by Alizarin red staining at 21 days. Data were compared group wise using ANOVA tests. Results: Irisin induced increased proliferation of primary hPDLCs and hOBs at all time points compared to untreated controls. This was confirmed by scratch assay where irisin enhanced migration of both hPDLCs and hOBs after 6 and 24 h compared to controls. Irisin treatment promoted osteogenic behaviour of both cell types by enhancement of extracellular matrix formation. In hPDLCs irisin increased expression of type I collagen, secretion of osteoblastogenesis related proteins osteocalcin and leptin, and calcium deposition/mineralization compared to controls at 21 days. In addition, to enhance calcium deposition/mineralization in hOBs, irisin increased expression of periostin, and secretion of osteoblastogenesis related proteins osteopontin, alkaline phosphatase and osteocalcin, as compared to controls at 21 days. Conclusions: Primary hPDLCs responded to irisin treatment with enhanced cell growth, migration, and matrix formation in vitro .